2022
DOI: 10.3389/fchem.2022.768426
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Doping of CaO as Catalyst for the OCM Reaction, a Reality Check

Abstract: In this study, first-row transition metal-doped calcium oxide materials (Mn, Ni, Cr, Co., and Zn) were synthesized, characterized, and tested for the OCM reaction. Doped carbonate precursors were prepared by a co-precipitation method. The synthesis parameters were optimized to yield materials with a pure calcite phase, which was verified by XRD. EPR measurements on the doped CaO materials indicate a successful substitution of Ca2+ with transition metal ions in the CaO lattice. The materials were tested for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…However, when the doping amount is increased, the atomic spacing of the dopant is shortened, which reduces the doping effect. 27 Therefore, the Ni-modified CaO adsorbent can enhance its surface electron-transfer ability and sintering resistance to some extent. However, nothing is known about how Ni affects the microscopic process of As 2 O 3 adsorption on CaO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the doping amount is increased, the atomic spacing of the dopant is shortened, which reduces the doping effect. 27 Therefore, the Ni-modified CaO adsorbent can enhance its surface electron-transfer ability and sintering resistance to some extent. However, nothing is known about how Ni affects the microscopic process of As 2 O 3 adsorption on CaO.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was discovered that the doping of trace amounts of nickel in CaO significantly improves its electronic characteristics and the redox capacity of the adsorbed molecules. However, when the doping amount is increased, the atomic spacing of the dopant is shortened, which reduces the doping effect …”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the performance of CaO is improved by doping it with different materials and transition metals (e.g., Ag, Ni, etc.) [35,36]. This is because the introduction of dopants creates new states in the oxide gap, which improves its performance.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of atomically dispersed platinum atoms not only in the first MgO layer but also in the second layer calls to mind reports of atomically dispersed supported metals in which the metals have been regarded as support-embedded. The literature includes many examples of doped solid catalysts, with dopants in various and difficult-to-determine subsurface sites. , The term embedded commonly implies substitution of an additive or doped metal into sites such as cation vacancies of supports typified by metal oxides, but this term is vague because the substitution can occur both at the surface and within the bulk of the support …”
mentioning
confidence: 99%
“…37−39 The literature includes many examples of doped solid catalysts, with dopants in various and difficult-todetermine subsurface sites. 40,41 The term embedded commonly implies substitution of an additive or doped metal into sites such as cation vacancies of supports typified by metal oxides, 37 but this term is vague because the substitution can occur both at the surface and within the bulk of the support. 42 The Journal of Physical Chemistry Letters Some prior catalysis investigations acknowledge that subsurface platinum could contribute to reactivity, but the authors did not explicitly consider these sites in models (e.g., ref 43).…”
mentioning
confidence: 99%